Go Pong: Media Pembelajaran Teknik Dasar Tenis Meja Berbasis Android - Irfan Dita Pratama; Tubagus Herlambang; Buyung Kusumawardhana; Ibnu Fatkhu Royana (Universitas PGRI Semarang, 2020)
Go Pong: Learning Media for Basic Techniques of Table Tennis Based on AndroidThis research used development research which was Research and Development (R&D) with 8 stages. The subject of this study was the eighth grade students of Junior High School of 1 Juwana. The data analysis techniques used were test and non-test techniques in the form of interview, observation, questionnaire, and documentation. The results showed the effectiveness test of Go Pong media on learning outcomes that obtained an n-gain index was 0.486 and 0.374 with moderate criteria. While learning outcomes used book got the results 0.263 and 0.07 with moderate criteria. The percentage of Go Pong media completeness was superior at 60% while using books was only 40%. The conclusion of this study is that Go Pong media is very effective to be used for learning compared to book media.Keywords: learning outcomes, Go Pong media, basic techniques of table tennis. Penelitian ini menggunakan penelitian pengembangan Research and Development (R&D) dengan 8 tahap. Subyek penelitian ini adalah siswa kelas VIII SMP Negeri 1 Juwana. Teknik analisis data yang dilakukan adalah teknik tes dan nontes berupa wawancara, observasi, angket, dan dokumentasi. Hasil penelitian menunjukkan uji keefektifan media Go Pong terhadap hasil belajar yang memperoleh indeks n-gain sebesar 0,486 dan 0,374 dengan kriteria sedang. Sedangkan hasil belajar menggunakan buku mendapatkan hasil 0,263 dan 0,07 dengan kriteria sedang. Presentase ketuntasan media Go Pong lebih unggul yaitu 60% sedangkan memakai buku hanya 40%. Simpulan penelitian adalah media Go Pong sangat efektif digunakan untuk pembelajaran dibandingkan menggunakan media buku.Kata kunci: hasil belajar, media Go Pong, teknik dasar tenis meja.